DYNAMIC QUALITY MANAGEMENT APPROACH FOR LEAN MANAGEMENT SYSTEMS: A FUTURE PERSPECTIVE FOR COMPANIES? - Gök, Mehmet Şahin; Arici, Tugkan (Pressacademia, 2016)
In today's highly competitive and rapidly changing business environment, the issues of efficiency and productivity are essential concerns for all industries. Dynamic quality management has emerged as an innovation model that integrates systematic process concerns into business processes. Considering the lean management system philosophy, which mainly aims to eliminate waste by using effective tools, integrated dynamic quality management has become a key factor for increasing effectiveness. Accordingly, this study mainly aims to examine the relationship between dynamic quality management and lean production systems through the whole business processes. This ambiguous relationship is theoretically analyzed by using recent studies in the management field as a meta-analysis method. The study findings demonstrate how to build the necessary business model for achieving success in dynamic quality management approach. Consequently, the insightful comments are provided for both academic researchers and sectoral managers.
Global Business Research Congress (GBRC) -- MAY 26-27, 2016 -- Istanbul, TURKEY
Keywords: Dynamic quality management; lean management; meta-analysis method